Controlled Tetradeuteration of Straight‐Chain Fatty Acids: Synthesis, Application, and Insight into the Metabolism of Oxidized Linoleic Acid. Issue 25 (26th April 2022) - Watanabe, Ayako; Hama, Kotaro; Watanabe, Kohei; Fujiwara, Yuko; Yokoyama, Kazuaki; Murata, Shigeo; Takita, Ryo
Abstract: We describe a concise and reliable protocol for the precisely controlled tetradeuteration of straight‐chain fatty acids (FAs) at the α‐ and β‐positions that is generally applicable to a variety of FAs, including trans ‐FAs, polyunsaturated FAs (PUFAs), and their oxidized derivatives. The precisely controlled introduction of four deuterium atoms into the FAs enables their persistent and quantitative tracking by LC‐MS/MS analysis based on their molecular structures. In addition, the phosphatidylcholine (PC) species prepared from the tetradeuterated FAs thus obtained give a diagnostic peak, namely, a phosphocholine fragment that contains deuterium, in the LC‐MS/MS analysis. With these features, the metabolism of a representative oxidized linoleic acid, that is, hydroxyoctadecadienoic acid (HODE), was investigated, leading to the identification of acyltransferases that transfer the acyl moiety derived from HODE to lysophosphatidylcholine. Abstract : A concise protocol for the precisely controlled tetradeuteration of straight‐chain fatty acids at the α‐ and β‐positions has been developed. The use of four deuterium atoms in fatty acids as well as a diagnostic peak of phosphatidylcholines thus obtained enabled the identification of acyltransferases that transfer the acyl moiety derived from an oxidized linoleic acid, hydroxyoctadecadienoic acid (HODE), to lysophosphatidylcholine.